Hylopoly-Bag: Environmentally Friendly Bioplastic Innovation Made from Dragon Fruit (Hylocereus polarizes) Peel Waste to Support Golden Indonesia 2045 - Tri Sunan Agung; Belinda Safa Salsabila Zuhri; Shinfi Wazna Auvaria (Jurnal Penelitian Pendidikan IPA, 2024)
Hylopoly-bag is a bioplastic bag from red dragon fruit (H. polyrhizus) skin waste. This research aims to discuss 2 things, namely the quality of hylopoly-bags and the realization of hylopoly-bags in supporting Golden Indonesia 2045. Experimental research uses descriptive quantitative methods. The independent variable is a ratio of dragon fruit peel extract and polyvinyl acetate of 2:1, 4:1, and 6:1, with the final quality of hylopoly-bag as the dependent variable. The analysis technique includes 6 methods: hylopoly-bag chemical content test, functional groups, permeability, elasticity, biodegradation rate, and SWOT. The results of the hylopoly-bag cellulose content were 6.32% and the functional groups consisted of C, H, and N. The analysis concluded that after the 28th day, the hylopoly bag had degraded the most, reaching 92 and 8% of the total initial weight of 7 grams. Hylopoly-bag has a water absorption capacity of up to 17% for 10 minutes and the average elasticity of hylopoly-bag is 4.65 x 104 N/m2. Hylopoly-bag can support Golden Indonesia 2045, especially the sub-pillars of scientific contribution and commitment to the environment.